2014
DOI: 10.9775/kvfd.2013.10175
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Clostridium difficile in Raw Bovine, Ovine, Caprine, Camel and Buffalo Milk in Iran

Abstract: SummaryThis study was conducted to determine the prevalence of Clostridium difficile in raw milk in Iran. From January to August 2013, a total of 430 raw milk samples from bovine (n=135), ovine (n=100), caprine (n=80), buffalo (n=49) and camel (n=66) were purchased from randomly selected from 111 dairy farm in Iran and were evaluated for the presence of C. difficile. In this study, only 2 of 135 bovine milk samples (1.43%) were contaminated with C. difficile. One of the two C. difficile strains was positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…From 1,939 studies identified, 79 fulfilled the inclusion criteria for meta-analysis, involving >231 authors and 25 countries over the past 37 years. The list of studies in chronological order from North America (10,16,17,, Europe (21,, Asia (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96), Africa (97)(98)(99)(100)(101)(102), Oceania (18, 103) (Australia/New Zealand) and Latin American (104,105) is presented in Table 1 (10, 16-18, 21, 30-32, 34-61, 63-78, 80-93, 96-110). The majority of studies, 92.4% (73 of 79 studies) since 2007, encompass 96.4% of all food samples tested (over the last 12 years) making this analysis current and relevant to the modern concerns of food transmission of CD via the food supply.…”
Section: Global Distribution Of Studies Reporting C Difficile In Foomentioning
confidence: 99%
“…From 1,939 studies identified, 79 fulfilled the inclusion criteria for meta-analysis, involving >231 authors and 25 countries over the past 37 years. The list of studies in chronological order from North America (10,16,17,, Europe (21,, Asia (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96), Africa (97)(98)(99)(100)(101)(102), Oceania (18, 103) (Australia/New Zealand) and Latin American (104,105) is presented in Table 1 (10, 16-18, 21, 30-32, 34-61, 63-78, 80-93, 96-110). The majority of studies, 92.4% (73 of 79 studies) since 2007, encompass 96.4% of all food samples tested (over the last 12 years) making this analysis current and relevant to the modern concerns of food transmission of CD via the food supply.…”
Section: Global Distribution Of Studies Reporting C Difficile In Foomentioning
confidence: 99%
“…https://doi.org/10.1101/19012450 doi: medRxiv preprint . Contextualization of food items tested in America, 6,18,19,34,35, , Europe, 23, Asia, [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] Africa, [104][105][106][107][108][109] and Oceania, 20,110,111 . For a historic narrative see is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…Te presence of both 027 and 078 ribotypes has been described in C. difcile strains isolated from human clinical infections [63,64]. Te presence of both 027 and 078 ribotypes has also been reported in C. difcile strains isolated from a wide range of foods, particularly meat [38,39,43,[65][66][67][68], milk [69], vegetable [70,71], and ready-to-eat food [72,73] samples. Ribotype 078 was also detected in C. difcile isolates from raw meat in the Netherlands [25].…”
Section: Distribution Of Toxigenic Genes Tablementioning
confidence: 93%